Precision agriculture with monitoring system / Irfan Arif Mohd Zaher - Mohd Zaher, Irfan Arif (2020)
Precision Agriculture with Monitoring System is an automated agriculture system, which can be used by all level of society. This paper proposes a Precision Agriculture with Monitoring System to monitor sensor readings and control actuator to maintain the soil condition in the optimum range. The main objective of this project is to automatically supply water, acid and alkaline solution when the readings exceed optimum range and alert farmers when soil condition reach extreme range because it could lead to drying of crops. The software used in this project is Lab VIEW since it is compatible with NI myRIO. NI myRIO is used as a platform to interface the sensors, which are soil moisture sensor, soil pH sensor and temperature sensor. The actuator, which is water pump is also interfaced via myRIO. Besides that, this project can help users to continuously monitor the crops and makes analysis based on the soil moisture content and soil pH value parameters. It informs the users of causes of extreme conditions that leads to deficiency of water or excess of acid level in the soil.